A metagenomic approach from aphid's hemolymph sheds light on the potential roles of co-existing endosymbionts. Issue 1 (December 2015) - De Clerck, Caroline; Fujiwara, Akiko; Joncour, Pauline; Léonard, Simon; Félix, Marie-Line; Francis, Frédéric; Jijakli, M.; Tsuchida, Tsutomu; Massart, Sébastien
Abstract Background Aphids are known to live in symbiosis with specific bacteria, called endosymbionts which can be classified as obligate or accessory.Buchnera aphidicola is generally the only obligatory symbiont present in aphids, supplying essential nutrients that are missing in the plants phloem to its host.Pentalonia nigronervosa is the main vector of the banana bunchy top virus, one of the most damageable viruses in banana. This aphid is carrying two symbionts:B. aphidicola (BPn) andWolbachia sp. (wPn). The high occurrence ofWolbachia in the banana aphid raises questions about the role it plays in this insect. The goal of this study was to go further in the understanding of the role played by the two symbionts inP. nigronervosa. To do so, microinjection tests were made to see the effect of wPn elimination on the host, and then, high-throughput sequencing of the haemolymph was used to analyze the gene content of the symbionts. Results We observed that the elimination of wPn systematically led to the death of aphids, suggesting that the bacterium could play a mutualistic role. In addition, we identify and annotate 587 and 250 genes for wPn and BPn, respectively, through high-throughput sequencing. Analysis of these genes suggests that the two bacteria are working together for the production of several essential nutrients. The most striking cases are for lysin and riboflavin which are usually provided byB. aphidicola alone to the host. In the banana aphid, the genes involved in the production pathways of these metabolites are shared between the two bacteria making them both essential for the survival of the aphid host. Conclusions Our results suggest that a co-obligatory symbiosis betweenB. aphidicola andWolbachia occurs in the banana aphid, the two bacteria acting together to supply essential nutrients to the host. This is, to our knowledge, the first timeWolbachia is reported to play an essential role in aphids.